PENERAPAN PEMBIAYAAN AKAD IJARAH MULTI JASA DI PT.BPR SYARIAH LAMPUNG TIMUR - Rohmah Habibah (EKSYDA: Jurnal Studi Ekonomi Syariah, 2025)
Multiservice Financing is a consumer financing product provided to customers to obtain benefits from various services, such as education, healthcare, employment, tourism, wedding services, and others. This study aims to explore the implementation of the Ijarah Multiservice Financing Contract at PT BPR Syariah Lampung Timur and to identify the strengths, weaknesses, opportunities, and threats (SWOT) related to its application. This research is a field study conducted at PT BPR Syariah Lampung Timur using both primary and secondary data sources. Data collection methods include observation, interviews, and documentation. The data collected were then analyzed using qualitative descriptive analysis. The SWOT analysis results indicate that PT BPR Syariah Lampung Timur utilizes its strengths to maximize opportunities, such as by implementing the ujrah/fee system as a source of bank income, adopting a proactive marketing approach (jemput bola), and collaborating with Bank Lampung, which is designated as one of the banks responsible for processing civil servants' salaries (PNS/CPNS).